Photodegradable Hydrogel Matrices for Spatiotemporal Control of Bacteria Transport and Delivery - Jeffrey A. Reed (22168271) (2025)
Stimuli-responsive hydrogels that provide controlled degradation can be used as bacteria delivery systems for advanced therapeutic applications. Here, we report the first use of photodegradable hydrogels as materials that can direct bacterial movement, tune mean bacteria speed, and control bacteria delivery through spatiotemporal control of degradation. Hydrogels were formed using base-catalyzed Michael addition reactions between photodegradable poly(ethylene glycol) (PEG) o-nitrobenzyl diacrylate macromers and PEG tetra-thiol cross-linkers within microfluidic channels. Nutrient gradients were generated across the channel, and micron-scale regions of the hydrogel were partially degraded by exposure to controlled doses (2.1–168 mJ/mm2) of patterned 365 nm light. Hydrogel degradation was then characterized in situ using fluorescence visualization of fluorescein-labeled hydrogels. Following characterization, Bacillus subtilis expressing green fluorescent protein was introduced into the device, and its movement up the nutrient gradient was monitored using time-lapse fluorescence microscopy to enable a systematic study of bacteria chemotaxis through the hydrogels at varied levels of degradation. B. subtilis showed minimal adhesion to partially degraded PEG hydrogels, and bacteria mean speed and mean directional change were tunable according to the level of hydrogel photodegradation, with a 2.6-fold difference in mean cell speed measured across the partially degraded hydrogel regions. Finally, the ability to alter bacteria speed and directionality through tunable degradation and without significant adhesion was used to achieve controlled release profiles of bacteria to delivery sites. These findings advance the use of PEG-based hydrogel materials as delivery vehicles for bacterial therapeutic applications and other living material applications that require controlled bacteria transport.